Synthesis and Characterization of Hierarchical CeO2 Spherical Nanoparticles for Photocatalytic Degradation of Methylene Blue - Huu Trinh, Le; Duc Cuong, Nguyen; Dang Trung, Do; Van Hieu, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 37 No 4DO - 10.25073/2588-1124/vnumap.4646, 2021)
: In this study, hierarchical CeO 2 spherical nanoparticles were fabricated by the polyol method using Ceri (III) acetate hydroxide, sodium hydroxide, and triethylene glycol as precursors. The product was characterized by XRD, SEM, and TEM. The results show that the cerium oxide spherical nanoparticles built from primary nanoparticles with the average size of ~5 nm, exhibited dispersion and uniform size and shapes with their average particle diameter of ~50 nm in size. With such a good morphology, CeO 2 material possessed good catalytic activity for the decomposition of methylene blue (MB), in which the material was synthesized at a hydrothermal temperature of 80 o C (CeO 2 -80) for the best MB decomposition performance.